2023
DOI: 10.1038/s41598-023-28553-9
|View full text |Cite
|
Sign up to set email alerts
|

Experiencing sweet taste is associated with an increase in prosocial behavior

Abstract: Taste may be the first sense that emerged in evolution. Taste is also a very important sense since it signals potential beneficial or dangerous effects of foods. Given this fundamental role of taste in our lives, it is not surprising that taste also affects our psychological perception and thinking. For example, previous research demonstrated remarkable psychological effects of sweet taste experiences, suggesting that sweetness may be a source domain for prosocial functioning. Recent research reports that brie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…This shift could have included monogamous pair bonding ( 4 , 52 , 59 61 ). Of note is that the experience of sweet taste is associated with romantic feelings and an increase in prosocial behaviors ( 62 65 ), while bitter taste has been associated with moral disgust ( 66 ). It is not known how the experience of fat consumption influences social or other behaviors, but these results would lead to the prediction that fat intake may increase positive social behaviors as well as brain nutrient supply.…”
Section: Discussionmentioning
confidence: 99%
“…This shift could have included monogamous pair bonding ( 4 , 52 , 59 61 ). Of note is that the experience of sweet taste is associated with romantic feelings and an increase in prosocial behaviors ( 62 65 ), while bitter taste has been associated with moral disgust ( 66 ). It is not known how the experience of fat consumption influences social or other behaviors, but these results would lead to the prediction that fat intake may increase positive social behaviors as well as brain nutrient supply.…”
Section: Discussionmentioning
confidence: 99%
“…As such, our research opens up promising avenues for integrated investigation into the influence of other tastes or other sensory modalities on temporal perspective preferences that bears on mutual arousal of emotion and its attendant motivation. For example, studies have shown that sweet taste can have a favorable effect on hypothetical romantic relationships (Ren et al, 2015) and promote prosocial behaviors (Meier et al, 2012), both of which exemplify approach behavior (Schaefer et al, 2023). It would be interesting to find out whether experiencing sweet taste would tilt the taster toward the ego-moving perspective because of its being positive and a catalyzer for approach-related social cognition and behavior.…”
Section: Contributionsmentioning
confidence: 99%
“…Apart from influencing the selection of medicinal plants, taste can also sway affective responses and the consumption of these plants (Geck et al 2017). For instance, food items rich in polyphenols, which manifest bitter and astringent qualities, are not readily accepted by children (Canivenc-Lavier et al 2019), while sweet substances are preferred by humans (Venditti et al 2020, Schaefer et al 2023. These reactions might have evolved as a mechanism to navigate nature-derived chemicals, where bitter and sour flavors denote toxic compounds (Glendinning 1994) and sweet and salty tastes signify energy sources (Hayes & Johnson 2017).…”
Section: Introductionmentioning
confidence: 99%